Elimination of mother‐to‐child transmission of HIV and syphilis: A dual approach in the African Region to improve quality of antenatal care and integrated disease control. (29th April 2015) - Newman Owiredu, Morkor; Newman, Lori; Nzomo, Theresa; Conombo Kafando, Ghislaine; Sanni, Saliyou; Shaffer, Nathan; Bucagu, Maurice; Peeling, Rosanna; Mark, Jennifer; Diop Toure, Isseu
Abstract: The World Health Organization's (WHO) Strategic Framework for the Elimination of New HIV Infections among Children in Africa by 2015 identifies important synergies for the elimination of mother‐to‐child transmission of HIV and syphilis in terms of prevention interventions, implementation logistics and service delivery, monitoring and evaluation systems, and need for sustained political commitment. The WHO advocates the use of an integrated, rights‐based dual approach with partnerships and collaboration to make the best use of available resources. Through a consultative approach, six countries in the African Region committed to dual elimination and developed and implemented action plans for this purpose. Where interest and commitment are high, this may also be possible and effective in other African countries.